Gully’s monitoring: morfometric and sediments study at Brazil’s savanna - Alves, Roberto Reis; Alves, Ricardo Reis; Rodrigues, Silvio Carlos (Sociedade & Natureza, 2005)
Gully’s monitoring: morfometric and sediments study at Brazil’s savanna